Lexicon of Verbal Bullying (Ijime) in Japanese and Its Cultural Implications: An Ethnolinguistic Study of Degrading Diction - Sohi Bhatul Hamdi; Teguh Santoso (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
The phenomenon of ijime (bullying) remains a persistent social issue in Japanese society, exerting serious psychological effects on its victims. Among its most subtle yet pernicious forms are verbal ijime, or bullying through language, ridicule, and verbal humiliation intended to degrade an individual’s dignity. This study aims to identify the lexical forms employed in verbal ijime and examine their underlying cultural implications through a qualitative ethnolinguistic approach. Data were collected through in-depth interviews with native Japanese speakers, field observations in the Tokai region (Aichi, Gifu, and Mie), and analysis of documentation and field notes related to cases of verbal ijime. Research participants included victims and former victims of ijime, teachers, counselors, coworkers, and native speakers familiar with linguistic expressions of verbal bullying. Data analysis followed descriptive qualitative procedures, including transcription, reduction, classification of degrading lexicons, and interpretation of cultural meanings based on Duranti’s linguistic anthropology theory and Brown and Levinson’s politeness and speech act theories. Findings reveal that the lexical patterns of verbal ijime reflect Japan’s collective value system emphasizing wa (harmony), meiyo (honor), and social conformity. Derogatory expressions serve not only as emotional outlets but also as mechanisms that reproduce cultural norms reinforcing social hierarchy. Thus, language in verbal ijime functions as both a mirror of cultural ideology and an instrument of social control in Japanese society.